Factors and challenges influencing impression management practices among Arab researchers in mass communication on Academic Social Networks - Elkhattat, Dina; Anter, Alyaa (Frontiers in Research Metrics and Analytics, 2025)
The study aims to explore the motivations and challenges affecting the utilization of Academic Social Networks among Arab mass communication researchers. Identifying the impression management strategies and practices among them and highlighting the obstacles these researchers face. An online survey was applied, collecting a convenience sample consisting of 100 respondents from six Arab countries. Countries include Egypt, Saudi Arabia, the United Arab Emirates, Iraq, Palestine, and Morocco. The study Findings showed no statistically significant differences in the time spent on ASNs based on gender. However, the analysis indicated differences in service usage between males and females. The findings also revealed significant variations in impression management practices based on gender, which highlight concerns regarding gender equality among Arab researchers. The study's findings identified several obstacles that prevent Arab researchers in Mass Communication from fully utilizing academic social networks (ASNs). The respondents cited plagiarism as the most significant concern, with 39%. Findings highlight the need for further studies to explore these barriers. The study also recommends conducting more research studies to compare the influence of disciplines on ASN practices, investigate how the area of specialization impacts research practices by comparing theoretical and applied specializations, and examine how specialization affects the use of ASNs, allowing for a comparison of differences among researchers in the sciences, arts, and humanities.